2018
DOI: 10.1016/j.hpb.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Added value of CA19-9 response in predicting resectability of locally advanced pancreatic cancer following induction chemotherapy

Abstract: Adding CA19-9 response after induction chemotherapy seems useful in determining which patients with RECIST non-progressive LAPC should undergo exploratory surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 19 publications
10
92
1
Order By: Relevance
“…Although in our cohort limited patients with LAPC underwent neoadjuvant chemotherapy, a small difference in CEA and CA19-9 was seen, which suggests that besides tumour anatomy, tumour biology has to be taken into account in the treatment of PDAC patients. Furthermore, it has been suggested that a decrease (>30%) of CA19-9 level in LAPC patients during the course of neoadjuvant therapy, resulted in improved resection rates during surgical exploration, which confirmed the relevance of tumour biology in patient selection for surgery (van Veldhuisen et al 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Although in our cohort limited patients with LAPC underwent neoadjuvant chemotherapy, a small difference in CEA and CA19-9 was seen, which suggests that besides tumour anatomy, tumour biology has to be taken into account in the treatment of PDAC patients. Furthermore, it has been suggested that a decrease (>30%) of CA19-9 level in LAPC patients during the course of neoadjuvant therapy, resulted in improved resection rates during surgical exploration, which confirmed the relevance of tumour biology in patient selection for surgery (van Veldhuisen et al 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Postoperative normalization of serum CA19-9 after pancreatic resection for pancreatic cancer correlates with an improved prognosis compared to an increase or lower but still elevated value (4). CA19-9 can help predict which patients are suitable for resection after induction therapy for locally advanced pancreatic cancer (5). Pre-and post-treatment CA19-9 can also be used to evaluate the effect of chemotherapy on pancreatic cancer (6).…”
mentioning
confidence: 99%
“…This may lead to missed opportunities to resect. Previous prospective series showed only a 40% sensitivity of a CT-based RECIST partial response for resectability in patients with LAPC following induction chemotherapy 14 and no correlation with tumor size decrease with R0 resection. 6 In addition, vascular involvement and thus resectability is not accurately measured by CT-scan after FOLFIRINOX therapy.…”
Section: Discussionmentioning
confidence: 87%
“…19 Biomarkers such as CA19-9 and plasma microRNAs have been previously described to be useful in selecting patients for surgery after induction chemotherapy and should be used in addition to current imaging modalities. 14,20,21 The results of this study should be interpreted in light of several limitations. First, this was a non-blinded study, since the performing radiologist was aware of the outcomes of the restaging CT-scans.…”
Section: Discussionmentioning
confidence: 90%